Madrasah Diniyah Sebagai Pola Diseminasi Islam Moderat di Pesantren Mahasiswa Darussalam Keputih Surabaya - Mukaffa, Zumrotul (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
This paper attempts to unravel the important role of the Madrasah Diniyah under Darussalam Islamic Boarding School Keputih within the 10 November Institute of Technology Surabaya (ITS) environment with transnational Islamic movement. The organizers are fully aware of the importance of disseminating moderate Islamic values and positioning Madrasah Diniyah as mediation structure to develop tolerance ​​and to counter the formalization of khilafah within the Unitary State of the Republic of Indonesia. The santri did not only study a collection of kitab based upon their levels, but also explore the great ideas of moderate Islam in the country. The enrichment process was managed by reflecting students' knowledge with WIKI ASWAJA and ASWAJA NU websites, managed under PWNU Aswaja Study Center in East Java. Recent issues, such as the Caliphate and Islam Nusantara on the website are discussed with the bandongan-muhawarah method by involving all santri. The success of the Madrasah Diniyah Takmiliyah in the pesantren Darussalam as a mediating structure was marked by its ability to develop counter-discourse towards transnational Islamic movements in campus environment.